The Effect of Complementary Alternative Medicine for Anxiety on Cancer Patients - Se Young Jan; Fitriani Fitriani; Al Ihksan Agus (An Idea Nursing Journal, 2023)
Cancer is one of the main causes of mortality worldwide. Therefore, cancer is often associated with anxiety which can interfere with the quality of life in cancer patients. Anxiety causes dizziness, fast heart rate, difficulty breathing, and trembling. This study aimed to determine the anxiety of cancer patients receiving chamomile aromatherapy interventions. This type of research was quantitative research, using a quasi-experimental research design with a pre and posttest design without a control group. Scheme of pre-posttest design research design. The results of a study of 75 cancer patients at Stella Maris Makassar Hospital using the Wilcoxon alternative test showed that the p-value was 0.001 <0.05, so it can be concluded that there is an effect of chamomile aromatherapy on the level of anxiety in cancer patients. The analysis results obtained on the level of anxiety experienced by cancer patients before being given chamomile aromatherapy, namely as much as 45.3% experienced moderate anxiety and after being given chamomile aromatherapy as much as 8% experienced moderate anxiety. This shows that there is a significant change in the anxiety level of the respondents after being given chamomile aromatherapy. Keywords: Cancer, Chamomile Aromatherapy, Anxiety